2016
DOI: 10.15369/sujms.28.309
|View full text |Cite
|
Sign up to set email alerts
|

Determination of <i>In-vivo</i> Glenohumeral Translation during Loaded and Unloaded Arm Elevation

Abstract: : An understanding of normal joint kinematics is essential to develop treatments that restore normal joint mechanics ; however, reports of kinematics during dynamic motion are rare. This study thus investigated glenohumeral GH translation in vivo during loaded and unloaded shoulder abduction. Nine healthy shoulders were studied from our patient cohort average age, 31 years . We created 3D models of the scapula and humerus using computed tomography CT images and recorded uoroscopic images during active abductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…We observed a load-induced increase in scapular rotation in healthy shoulders and in shoulders with rotator cuff tears. Glenohumeral translation changed with additional weight neither in healthy shoulders, as reported also by Nishinaka et al [ 30 ], nor in shoulders with rotator cuff tears during 30° abduction. Therefore, in this cohort, shoulders with rotator cuff tears and healthy shoulders appear to behave similarly under load, with upward scapular rotation increasing during 30° abduction so as not to alter glenohumeral joint stability.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…We observed a load-induced increase in scapular rotation in healthy shoulders and in shoulders with rotator cuff tears. Glenohumeral translation changed with additional weight neither in healthy shoulders, as reported also by Nishinaka et al [ 30 ], nor in shoulders with rotator cuff tears during 30° abduction. Therefore, in this cohort, shoulders with rotator cuff tears and healthy shoulders appear to behave similarly under load, with upward scapular rotation increasing during 30° abduction so as not to alter glenohumeral joint stability.…”
Section: Discussionmentioning
confidence: 56%
“…Some of the inconsistencies in literature regarding kinematics may arise from the different acquisition techniques, such as conventional radiographs [ 9 , 23 , 25 , 26 ] or single/dual-plane fluoroscopy combined with three-dimensional (3D)-to-two-dimensional (2D) model-to-image registration techniques [ 20 , 22 , 24 , 27 30 ]. In addition, shoulder kinematics may differ under quasistatic and dynamic conditions [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Teyhen et al [ 9 ] found a more superior humeral head position during abduction, and similar results were reported by Chopp et al [ 7 ] up to 90° abduction. Only Nishinaka et al [ 8 ] compared shoulder kinematics of loaded (3 kg) and unloaded arm abduction, but did not assess the differences between conditions, and reported an average of 2 mm translation from 0° to 90° abduction.…”
Section: Introductionmentioning
confidence: 99%